Full scale study of Class A biosolids produced by thermal hydrolysis pretreatment and anaerobic digestion. (August 2018) - Wang, Xuanzhao; Andrade, Natasha; Shekarchi, Jessica; Fischer, Sarah J.; Torrents, Alba; Ramirez, Mark
Highlights: Class A biosolids produced by thermal hydrolysis and anaerobic digestion processes. Fecal coliforms varied during startup and reached low levels in full operation. Metals content increased in Class A compared to Class B biosolids. Class A contains high levels of total nitrogen and phosphorus but low potassium. Abstract: Biosolids are the solid by-product of wastewater treatment and contain high-organic matter and nutrient content, which can be utilized in food production and gardening. In 2014, this study's target nutrient recovery facility (NRF) in the Mid-Atlantic region of the U.S. adopted thermal hydrolysis pretreatment (THP) and anaerobic digestion (AD) to upgrade biosolids from Class B (lime-stabilized) to Class A. The pathogen, nutrients, and metals contents were compared with that of Class B biosolids from the same facility throughout a one-year period. Following optimization and equilibrium, stable biosolids were produced that satisfied all Environmental Protection Agency (EPA) Class A biosolids standards. Class A biosolids produced had fecal coliform density consistently below the 1000 MPN/g d.w. limit set by the EPA, at 35.85 ± 81.10 MPN/g d.w. ( n = 301). Metal concentrations were greater in Class A than Class B biosolids as a result of biosolids mass reduction, but these levels were substantially lower than regulatory limits. Metal concentrations were (in mg/kg d.w.): As = 6.43 ± 0.400 (n = 141), Cd = 3.39 ± 0.117 (n = 147), Cr = 88.4 ± 2.00 (n = 148), Cu = 401 ± 9.81 (n = 148), Pb = 68.1 ± 2.19 (n = 148), Hg = 1.21 ± 0.116 (n = 148), Mo = 14.9 ± 0.321 (n = 148), Ni = 23.8 ± 0.911 (n = 146), Se = 10.0 ± 0.573 (n = 140), Zn = 778 ± 14.9 (n = 148), K = 850 ± 21.7 (n = 134). In addition, Class A biosolids were rich in total nitrogen (N) and higher in total phosphorus (TP), but low in potassium (K) content. Concentration of K was 850 ± 21.7 mg/kg d.w. (n = 134), TKN was 52, 000 ± 13, 300 mg/kg d.w. (n = 43), TP was 34, 500 ± 6130 mg/kg d.w. (n = 42), and ammonia-N was 7860 ± 1350 mg/kg d.w. (n = 43).